Kelayakan Aksesoris Rambut Dengan Bahan Dasar Kulit Bawang Putih (Allium Sativum) (Beauty and Beauty Health Education, 2023)
Abstract. Garlic peel is only considered as garbage, processing garlic peel is only used for herbal medicine ingredients, a mixture of organic fertilizers and handicrafts such as wall hangings and table decorations. Researchers took the initiative to use garlic skin as hair accessories. The purpose of the study was to determine the feasibility of garlic skin as a basic material for making hair accessories using sensory tests and preference tests. This type of research is experimental. The research object is 3 hair accessories. The validity of the instrument using expert judgment includes 3 Lecturers of the Department of Family Welfare Education. The research subjects were 3 expert panelists for product validity including Beauty Assessor LSP ESCRINS, Accessories shop owner Valerian Artisan, and Art Director Lie Kuang Salon, 3 expert panelists for sensory testing including DPC Chairman Tiara Kusuma Semarang Regency, Chairperson of Harpi Melati Branch Pringapus Karangjati, shop owner Sari Accessories and 20 respondents who own salons and make-up studios. Methods of data collection using observation and documentation. The data analysis method used descriptive percentage. The results of the product validity test were declared very valid with an average result of 94%. Sensory test results were declared very feasible with an average result of 94%. The results of the preference test by salons and make-up studios were stated to be very favorable with an average result of 89%. Conclusions (1) Hair accessories products made from garlic skin are declared "very valid" through the product validator test. (2) Hair accessories products made of garlic skin are declared "very feasible" based on sensory test results (3) Hair accessories products made of garlic skin are declared "very favorable" based on the preference test. Suggestions for this research can be used as material in socialization and training activities to improve skills, insights and create new jobs. Keywords: feasibility of hair accessories with garlic skin as the basis Abstrak. Kulit bawang putih selama ini hanya dianggap sebagai sampah, pengolahan kulit bawang putih hanya digunakan untuk bahan obat herbal, campuran pupuk organik dan kerajinan tangan seperti hiasan dinding dan hiasan meja. Peneliti berinisiatif untuk memanfaatkan kulit bawang putih menjadi aksesoris rambut. Tujuan penelitian adalah mengetahui kelayakan kulit bawang putih sebagai bahan dasar pembuatan aksesoris rambut dengan menggunakan uji inderawi dan uji kesukaan. Jenis penelitian adalah experimen. Objek penelitian 3 aksesoris rambut. Validitas instrumen menggunakan expert judgement meliputi 3 Dosen Jurusan Pendidikan Kesejahteraan Keluarga. Subjek penelitian 3 panelis ahli untuk validitas produk meliputi Asesor Kecantikan LSP ESCRINS, Owner toko aksesoris Valerian Artisan, dan Art Director Lie Kuang Salon, 3 panelis ahli untuk uji Inderawi meliputi Ketua DPC Tiara Kusuma Kabupaten Semarang, Ketua Harpi Melati Ranting Pringapus Karangjati, Pemilik toko Sari Aksesoris dan 20 responden pemilik salon dan sanggar rias. Metode pengumpulan data menggunakan observasi dan dokumentasi. Metode analisis data menggunakan deskriptif persentase. Hasil uji validitas produk dinyatakan sangat valid dengan hasil rata-rata 94%. Hasil uji inderawi dinyatakan sangat layak dengan hasil rata -rata 94%. Hasil uji kesukaan oleh salon dan sanggar rias dinyatakan sangat disukai dengan hasil rata-rata 89%. Simpulan (1) Produk aksesoris rambut dengan bahan dasar kulit bawang putih dinyatakan “sangat valid” melalui uji validator produk. (2) Produk aksesoris rambut dengan bahan dasar kulit bawang putih dinyatakan “sangat layak” berdasarkan hasil uji inderawi (3)Produk aksesoris rambut dengan bahan dasar kulit bawang putih dinyatakan “sangat disukai” berdasarkan uji kesukaan. Saran penelitian ini dapat dijadikan materi dalam kegiatan sosialisasi dan pelatihan untuk meningkatkan keterampilan, wawasan dan menciptakan lapangan pekerjaan baru. Kata Kunci : Kelayakan Aksesoris Rambut Dengan Bahan Dasar Kulit Bawang Putih